The role and practices of online stakeholders - Wischmeyer, Thomas (Human Rights, Digital Society and the Law, 2019)
When the internet began to take off in the early 1990s, neither the legal concept nor the business model of an online intermediary truly existed. This chapter focuses on the role and practices of online stakeholder's starts by analysing the discussions about intermediary responsibility. It discusses the success of the initiatives in terms of horizontal governance. Numerous stakeholder-led initiatives analyse the obligations of online intermediaries in protecting fundamental rights online and propose more or less detailed guidelines for its members and for politics. The diversity of the stakeholder-led initiatives and the very limited output, which especially the more prominent of these initiatives produce, make it difficult to identify the emergence of common standards or principles. The stakeholder initiatives analysed show both the potential and the difficulties of intermediary self-regulation. The efforts of information and communication technologies companies and other online stakeholders to develop codes of conduct and to set common technical standards can be called limited at best.